2017
DOI: 10.29332/ijssh.v1n3.55
|View full text |Cite
|
Sign up to set email alerts
|

Improving cooperative performance through human resource development efforts

Abstract: Improving cooperative performance as one of the national and regional reconstruction teachers should be continuously carried out unlike the steps and anticipation by the many cooperatives that are bankrupt or disabled. The one aspect that needs to be improved was the aspect of Human Resources (HR) becomes manager and management of existing cooperatives. In order to realize it, the Department of Cooperatives and UMKM Bali Province has implemented various programs to improve the performance of cooperatives human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…This is a continuous learning process that deepens an employee's understanding for their values, interests, talents, personal attributes, and strengths their competencies. Martini et al, (2017), stated that HR is organization part that should carry out important activities. Looking at HR is very important in an organization or company.…”
Section: Resultsmentioning
confidence: 99%
“…This is a continuous learning process that deepens an employee's understanding for their values, interests, talents, personal attributes, and strengths their competencies. Martini et al, (2017), stated that HR is organization part that should carry out important activities. Looking at HR is very important in an organization or company.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the continued exposure to these stresses in combination with the presence of the predisposing factors the further progression of the defect will occur. 1,2 Furthermore, it was found that the severity of the NCCL increase with the age, 8 also the dimension and number of these defects increase with age. 1,8 Generally, the removal of the etiological factors of the NCCLs and/or replacement of the lost hard tooth structure can promote an enhancement in aesthetics and decrease the possible hypersensitivity which resulted because of these lesions.…”
Section: Introductionmentioning
confidence: 99%
“…This means that cooperatives do not only have the goal of seeking profit but also achieve mutual prosperity. The cooperative has a purpose for the welfare of members not for capital (Martini, Lasmi, Jaya and Sutrisni, 2017).…”
Section: Introductionmentioning
confidence: 99%